Chemistry at the tip of brushes: Teaching chemistry through makeup for black skin - Serbeto, Victoria Martins; Senra, Jaqueline Dias; de Souza, Elizabeth Teixeira (Seven Editora, 2024)
According to an interview conducted by the cosmetics company AVON, about 46% of the 1000 black women interviewed have difficulties finding makeup for black skin tones. This research highlights the persistent difficulty faced by Black-skinned individuals in finding makeup products that suit their skin tone, leading many to resort to improvised solutions during the makeup process. In this context, the proposed work aims to explore the relevance of makeup for black skin as an educational tool in the teaching of chemistry. The planned activities aim not only to make students aware of the scarcity of foundation options available for the various shades of black skin, but also to connect this problem with the chemical principles underlying the formulation of cosmetics. In this way, students will be encouraged to reflect on how the science of chemistry can be applied to solve societal issues and promote inclusivity, while also deepening their understanding of fundamental chemical concepts. In addition to promoting self-knowledge about black identity, the approach to makeup for black skin as a tool in the teaching of chemistry seeks to bring students closer to the discipline in a playful way. This is done through an active methodology, which includes hands-on experimentation and a quiz on Google Forms to understand the difficulties students face when looking for makeup suitable for black skin tones. DOI:https://doi.org/10.56238/sevened2024.015-012